Determinants of Concurrent Motor and Language Recovery during Intensive Therapy in Chronic Stroke Patients: Four Single-Case Studies - Primaßin, Annika; Scholtes, Nina; Heim, Stefan; Huber, Walter; Neuschäfer, Martina; Binkofski, Ferdinand; Werner, Cornelius J. (Frontiers in Neurology, 2015)
Despite intensive research on mechanisms of recovery of function after stroke, surprisingly little is known about determinants of concurrent recovery of language and motor functions in single patients. The alternative hypotheses are that the two functions might either “fight for resources” or use the same mechanisms in the recovery process. Here we present follow-up data of four exemplary patients with different base levels of motor and language abilities. We assessed functional scales and performed exact lesion analysis to examine the connection between lesion parameters and recovery potential in each domain. Results confirm that preservation of the corticospinal tracts is a neural predictor for good motor recovery while preservation of the arcuate fasciculus is important for a good language recovery. However, results further indicate that even patients with large lesions in corticospinal tract, arcuate fasciculus and superior longitudinal fasciculus, respectively, are able to recover their motor/language abilities during intensive therapy. We further found some indicators of a facilitating interaction between motor and language recovery. Patients with positive improvement of motor skills after therapy also improved in language skills, while the patients with no motor improvements were not able to gain any language recovery.